Design and experimental validation of a new radiolabeled analog of N-(3-hydroxy-4-methoxy-phenyl-methyl) ferrocene-carboxamide (VFC) targeting the TRPV1 receptor - Tesnim Dallegi; Syrine Ben Hassen; Nedra Rached; Farah Menjji; Roufaida Abassi; Ameur Cherif; Soumaya Kouidhi; Mouldi Saidi; Amor Mosbah (Elsevier, 2024)
The TRPV1 receptor has been recognized to play a role in cancer development, being overexpressed in prostate, breast, lung, and colon cancers. Since TRPV1 activation promotes cancer cell proliferation, invasion, and migration, TRPV1 antagonists may show potential as anti-cancer agents. Capsaicin and capsaicinoids are phytochemicals derived from homovanillic acid found in abundance in chili peppers and responsible for its pungent properties. Capsaicin acts as a potent agonist of TRPV1 with recognized antineoplastic properties. Here, we employ computational approaches including molecular modeling and docking to refine the 3D structure of human TRPV1 and assess its interaction with the newly synthesized N-(3-hydroxy-4-methoxyphenylmethyl)ferrocenecarboxamide (VFC) and its cyclopentadienyl tricarbonyl rhenium and technetium analogs. Radiolabeling of VFC with 99mTc was achieved by double ligand exchange to afford 99mTc-VFC in high radiochemical purity and yield. Biodistribution studies in mice demonstrated preferential accumulation of 99mTc-VFC in the bladder, liver, kidney, and lung. These findings may contribute to developing efficient TRPV1-targeted radiotracers for molecular imaging of tumors by SPECT.